(untitled) (Research, Society and Development, 2021)
Member loyalty is a crucial factor for the development of a cooperative, and it also provides members with conditions for maintenance and development. Considering this, the commercial transactions between the cooperative and its members reflect part of the interaction between them. This study aimed to investigate the economic participation of members of an agricultural cooperative in Rio Grande do Sul, Brazil, through documentary research consisting of data collection of the members’ transactions. Descriptive and multivariate statistical analyses were performed. The multivariate analyses showed the formation of three groups of associates. Group 1 represented the largest number of members and the lowest volume of business; group 2 included the most transactions of agricultural inputs; and group 3 represented the smallest number of members but with the greatest commercial importance and the highest volumes of invoicing and deposits. This differentiation allows the cooperative to identify the members’ profile and the most attractive transaction areas for different groups within the cooperative.